Concrete pavement design, construction, and performance - Delatte, Norbert J. (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'This book addresses the design, construction, and performance of concrete pavements. It sets out best practices for the construction of economical, long life concrete pavement by engineers in the public and private sectors. It also outlines first alternatives for concrete pavement solutions, and identifies their performance and behavior parameters. The text addresses materials selection and mix design; as well as pavement construction. It emphasizes the coherence of these three elements: materials, design, and construction, and covers highways, airport, industrial, and light duty pavements'--
Types of concrete pavements -- Sustainability and concrete pavements -- Performance -- Subgrades, subbases, and drainage -- Selection of concrete materials -- Mixture design and proportioning -- Design fundamentals -- Highway pavement design -- The mechanistic-empirical design guide -- Light-duty pavement design -- Pervious concrete pavements -- Airport pavement design -- Industrial pavement design -- Roller compacted concrete pavements -- Transitions and crcp reinforcement -- Subgrade and subbase construction -- Paving -- Finishing, texturing, curing, and joint sawing and sealing -- Concrete pavement maintenance -- Rehabilitation -- Overlays and inlays.
Includes bibliographical references : (pages 389-403) and index.
Keywords: Pavements, Concrete